2014
DOI: 10.1186/2049-6958-9-33
|View full text |Cite
|
Sign up to set email alerts
|

A novel diagnostic algorithm for chronic and subacute cough

Abstract: BackgroundCough remains the most common reason for patients to seek medical attention. We practised a novel diagnostic algorithm for chronic and subacute cough.MethodsChronic and subacute cough patients with normal chest X-ray results and without respiratory tract infections in the preceding eight weeks were recruited. The patients were divided into two groups: Group A, patients with typical symptoms and signs of postnasal drip syndrome (PNDS), asthma syndromes (AS) and gastroesophageal reflux disease (GERD); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, shortening the trials and educating the patients are imperative [29]. This study suggests that treating AS first [3] or AS and PNDS [30,31] simultaneously might be an alternative approach to the diagnosis of patients without typical symptoms or signs. However, further studies must be conducted for verification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, shortening the trials and educating the patients are imperative [29]. This study suggests that treating AS first [3] or AS and PNDS [30,31] simultaneously might be an alternative approach to the diagnosis of patients without typical symptoms or signs. However, further studies must be conducted for verification.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Lu and colleagues have demonstrated that overall therapeutic efficacy was comparable among the various protocols for empirically treating chronic and subacute cough. 22 …”
Section: Discussionmentioning
confidence: 99%